2018
DOI: 10.1504/ijw.2018.090187
|View full text |Cite
|
Sign up to set email alerts
|

Hydraulic interconnections study of Seropan-Ngreneng-Bribin underground rivers in Gunung Kidul karst area using tracer technique

Abstract: Series of studies have been conducted to investigate the hydraulic connection between Seropan underground rivers with other underground rivers in Gunung Kidul karst area. Stable isotopes composition, hydrochemical contents of collected samples from several sources around Seropan cave together with tracer tests that have been conducted in the area have helped us to establish hydraulic connection of Seropan underground river with adjacent underground rivers in Gunung Kidul karst area. Several tracer tests that h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
1
1
0
Order By: Relevance
“…This indicates that all of the surface water samples have undergone evaporation process before entering Lake Toba. The same phenomenon has also been observed by one of the authors during the study of "Hydraulic interconnections study of Seropan-Ngreneng-Bribin underground rivers in Gunung Kidul karst area using tracer technique" [19]. In the study, it was found that the slope of the linear relationship between  18 O and D values in the underground rivers was 4.77 which is very close to the present study result of 4.89.…”
Section: Surface Water Samplessupporting
confidence: 90%
See 1 more Smart Citation
“…This indicates that all of the surface water samples have undergone evaporation process before entering Lake Toba. The same phenomenon has also been observed by one of the authors during the study of "Hydraulic interconnections study of Seropan-Ngreneng-Bribin underground rivers in Gunung Kidul karst area using tracer technique" [19]. In the study, it was found that the slope of the linear relationship between  18 O and D values in the underground rivers was 4.77 which is very close to the present study result of 4.89.…”
Section: Surface Water Samplessupporting
confidence: 90%
“…O and D are part of the constituents of water molecules. Three different molecules of water that are normally used by hydrologists are H2 16 O (18), HD 16 O (19), and H2 18 O (20) in which the number in the bracket represents molecular mass. In nature, the abundance of HD 16 O and H2 18 O are extremely small compared with the abundance of H2 16 O.…”
mentioning
confidence: 99%